2016
DOI: 10.1186/s12886-016-0384-0
|View full text |Cite
|
Sign up to set email alerts
|

Colour Doppler analysis of ophthalmic vessels in the diagnosis of carotic artery and retinal vein occlusion, diabetic retinopathy and glaucoma: systematic review of test accuracy studies

Abstract: BackgroundColour Doppler analysis of ophthalmic vessels has been proposed as a promising tool in the diagnosis of various eye diseases, but the available diagnostic evidence has not yet been assessed systematically. We performed a comprehensive systematic review of the literature on the diagnostic properties of Colour Doppler imaging (CDI) assessing ophthalmic vessels and provide an inventory of the available evidence.MethodsEligible papers were searched electronically in (Pre) Medline, Embase and Scopus, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 28 publications
0
8
0
3
Order By: Relevance
“…It is interesting that vascular abnormalities could be present before development of disease. 30 For example, in normal tension glaucoma, the most common type of glaucoma in Asia, 18 blood flow measurements could help identifying eyes at risk.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is interesting that vascular abnormalities could be present before development of disease. 30 For example, in normal tension glaucoma, the most common type of glaucoma in Asia, 18 blood flow measurements could help identifying eyes at risk.…”
Section: Resultsmentioning
confidence: 99%
“…27,29 A systematic review from 2016 concluded however that CDI could not yet be recommended in a daily clinical setting due to the lack of standardized methods and solid studies of the method. 30 The lack of standardization makes it difficult to compare the different studies and evaluate the reproducibility of the method. The evaluated parameter in CDI measurements also vary in the different studies.…”
Section: Ultrasound CDImentioning
confidence: 99%
See 1 more Smart Citation
“…Doppler ultrasonography is a noninvasive technique that measures blood flow velocities in retrobulbar vessels (ophthalmic artery, OA; central retinal artery, CRA; short posterior ciliary arteries, PCAs). Several studies showed significant blood velocity derangements in the OA, CRA, and PCAs in glaucomatous patients, [15][16][17][18][19][20] and retrobulbar blood flow impairment has been associated to glaucoma progression. [17][18][19][20][21][22][23][24] Peak systolic and end-diastolic velocities (PSV, EDV) and Pourcelot's resistivity index (RI) have been traditionally considered in the hemodynamic evaluations of the retrobulbar vessels.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies showed significant blood velocity derangements in the OA, CRA, and PCAs in glaucomatous patients, [15][16][17][18][19][20] and retrobulbar blood flow impairment has been associated to glaucoma progression. [17][18][19][20][21][22][23][24] Peak systolic and end-diastolic velocities (PSV, EDV) and Pourcelot's resistivity index (RI) have been traditionally considered in the hemodynamic evaluations of the retrobulbar vessels. Recently, more attention has been given to additional arterial waveform parameters (WPs) commonly used in other medical specialties, such as WPs used in renal and hepatic arteries to predict transplantation failure, which might provide new insights in the characterization of retrobulbar hemodynamics in glaucoma patients.…”
Section: Introductionmentioning
confidence: 99%